STRATEGI OPTIMALISASI PENGELOLAAN ZAKAT, INFAQ, DAN SHADAQAH (ZIS) DALAM MENDORONG PENCAPAIAN SUSTAINABLE DEVELOPMENT GOALS (SDGS) PADA LAZISMU DIY - Aunillah, Radya Gayuh; Hidayah, Khusnul (COMPETITIVE, 2024)
Zakat, Infaq, and Shadaqah (ZIS) are the three pillars of Islam that play a significant role in both religious and social spheres, including poverty alleviation. Indonesia holds immense ZIS potential, reaching an estimated RP 327 trillion annually. Consequently, this research aims to analyse ZIS management's approach to poverty eradication and its methods, tactics, and optimization. The results show that LAZISMU Yogyakarta uses a well-organised ZIS management system with a focus on enhancing accountability, professionalism, efficiency, and effectiveness. The research was qualitative and used a case study design. The optimisation of ZIS management at LAZISMU Yogyakarta has made positive contributions to the attainment of SDGs, specifically poverty alleviation, as evidenced by the increased income of ZIS recipients in social and economic activities. This study recommends that LAZISMU Yogyakarta continue and enhance economic empowerment programs, strengthen partnerships, and further improve the accountability, professionalism, efficiency, and effectiveness of ZIS management.